#### Answer

$y' = 36x^2-16x+7$

#### Work Step by Step

In order to derivate this function you have to apply the power rule:
$\dfrac{d}{dx}(x^n)=nx^{n-1}$
$y' =12(3)x^2-8(2)x+7$
$y' = 36x^2-16x+7$

Published by
Pearson

ISBN 10:
0321749006

ISBN 13:
978-0-32174-900-0

$y' = 36x^2-16x+7$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.